SAT0506 Interest of Musculoskeletal Ultrasound in the Diagnosis of Calcium Pyrophosphate Dihydrate Deposition Disease. (10th June 2014) - Contant, E.; Ornetti, P.; Bohm, A.; Fortunet, C.; Maillefert, J.F.
Abstract : Objectives: To evaluate the sensitivity, specificity and predictive values of musculoskeletal ultrasound (US) in the diagnosis of calcium pyrophosphate dihydrate deposition disease (CPPD). Methods: Design: prospective monocentric study. Patients: consecutive hospitalized or outpatients with a mono, oligo, polyarthritis of unknown origin, available joint fluid for analysis, seen in the rheumatology department of the Dijon University Hospital between October 2012 and December 2013. Evaluation: X-rays (knees, wrists, feet, pelvis), joint fluid analysis (polarized-light microscopy), ultrasound assessment based on EULAR recommendations, using an Esaote Mylab 70 XVG equipped with a 10/18mHz probe, and involving the following joints: wrists, hips, knees, pubic symphysis, firts metatarsus and arthritic joints. The Frediani's sonographic criteria of CPPD were used. The ultrasound and joint fluid analysis were done blinded to other data. The final diagnosis was done by a college of 3 rheumatologists, experts in the management of arthritis and blinded to the results of US evaluation. Data analysis: the sensitivity, specificity, positive and negative predictive values of US evaluation for the diagnosis of CPPD arthritis were calculated using 2 gold standards, i.e, results of joint fluid analysis and final diagnosis of the experts. Results: Sixty six patients (46 men, 20 women, mean age=67.1±16.4 years; 38, 21 and 7 with mono, oligo or polyarthritis, respectively) were included. Arthritis was of less than 1 month duration in 45 patients. The final experts' diagnosis was CPPD disease (n=23), gout (n=15), association of CPPD and gout (n=5), rheumatoid arthritis (n=6), septic arthritis (n=5), post traumatic hydarthrosis (n=2), osteoarthritis (n=4), polymyalgia rheumatica (n=1), undifferentiated arthritis (n=3) and reactive arthritis (n=2). US assessment of the punctured joint: when the joint fluid analysis was used as gold standard, the sensitivity, specificity, positive and negative predictive values of US analysis for diagnosis of CPPD disease were 73.3%, 58.3%, 59.5% and 72.4%, respectively. When the experts' opinion was used as gold standard, the sensitivity, specificity, positive and negative predictive values of US analysis for diagnosis of CPPD disease were 85.7%, 65.8%, 64.9%, and 86.2%, respectively. US assessment of all joints: when the joint fluid analysis was used as gold standard, the sensitivity, specificity, positive and negative predictive values of US analysis for diagnosis of CPPD disease were 93.3%, 38.9%, 56.0% and 87.5%, respectively. When the experts' opinion was used as gold standard, the sensitivity, specificity, positive and negative predictive values of US analysis for diagnosis of CPPD disease were 100%, 41.0%, 54.0%, and 100%, respectively. Conclusions: These results suggest that US is useful in current practice, particularly to eliminate the diagnosis of CPPD disease. Results regarding specificity and positive predictive value might be considered as disappointing, but are not surprising, since it is well known from X-ray evaluations that patients can have CPPD deposits and suffer from arthritis of other origin, and since increasing sensibility usually induces a decrease in specificity. Rather than a gold standard for diagnosis, US should be used as an important tool for diagnosis, among others. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3533